Effect of dietary Ficus carica polysaccharides on the growth performance, innate immune response and survival of crucian carp against Aeromonas hydrophila infection. Issue 120 (January 2022) - Wang, Erlong; Chen, Xia; Liu, Tao; Wang, Kaiyu
Abstract: Ficus carica polysaccharides (FCPS), one of the most effective and important compo-nents in Ficus carica L., had been considered to be a beneficial immunostimulant and may be used in immunotherapy for animals and human. However, studies were little about the effect of FCPS used as immunomodulatory and the suitable dosage in fish. The present study investigated the effect of four different dietary levels of FCPS (0.1%, 0.2%, 0.4%, 0.8%) on the growth performance, innate immune responses and survival of crucian carp against Aeromonas hydrophila infection. The results showed that compared with control group, dietary FCPS had positive effects the growth performance (final weight, feed conversion ratio and survival rate) of crucian carp. FCPS induced significant higher (p < 0.05) leukocyte phagocytosis activity, serum bactericidal activity, lysozyme activity, com-plement C3, SOD activity and total protein level in the serum of crucian carp. Moreover, innate immune response of fish in FCPS groups increased first and then decreased with increasing dietary FCPS from 0.1% to 0.8%, and reached up to the peak in 0.4% dietary FCPS groups. Besides, the cumulative mortalities in FCPS groups were remarkably lower than that of control group when challenged with A. hydrophila, the relative percent survivals were 22.67%, 55.56%, 62.22% and 17.78% in 0.1% group, 0.2% group, 0.4% group and 0.8% group, respectively. These results suggested that dietary FCPS could improve the growth performance, innate immune response and disease resistance against A. hydrophila in fish, and the suitable dietary dose of FCPS was 0.4% in crucian carp. Highlights: Four different levels of FCPS all can improve the growth performance of crucian carp. Four different levels of FCPS all enhance innate immune responses and survival of crucian carp against A. hydrophila infection. The effect of different levels of FCPS on the innate immune response and survival was 0.4% FCPS >0.2% FCPS >0.1% FCPS >0.8% FCPS. The suitable dietary dose of FCPS was 0.4% in crucian carp.